IDENTIFIKASI POLA SEBARAN HORIZONTAL TEGAKAN JABON (Anthocephalus cadamba) HUTAN RAKYAT KOLABORASI ANTARA DESA JEPORO DAN PT. BUMN HIJAU LESTARI I (Kecamatan Jatipurno, Kabupaten Wonogiri, Jawa Tengah) - , ISTI MAWADDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The community forest at Jeporo has Jabon stand which is established by colaboration between community and PT BUMN Hijau Lestari I, a company which is engaged in eco-business based agro-forestry and cooperative. The community forest development requires proper planning for realizing principles of sustainable forestry. The sustainable planning requires yield regulation system. This yield regulation needs stand dynamic information which can be explore the stand structur dynamic. Stand dynamic can be described by studying the structure of horizontal stands. The research is conducted to identify structure of community Jabon stands and by applying the three-parameter Weibull distribution model. The samples are Jabon stands in owned land which has had diameter at breast height. The samples collection was conducted with purposive method. Jabon diameter distribution mapping was obtained from Weibull threeparameters, namely c (shape parameter), b (scale parameter), and a (location parameter). Parameterization was done by using maximum likelihood method and moments method. Fitting test was done with Kolmogorov-Smirnov test. The result indicates that the structure of Jabon stands pattern has diverse pattern which is ranged from even-aged stands to uneven-aged stands. The most appropriate estimation method to be applied is maximum likelihood method which contain 83,33% of parcels that was used as research samples.